THE USE OF ZOOM APPLICATION TO SUPPORT ONLINE LEARNING DURING PANDEMIC TIME FOR STUDENTS OF ENGLISH DEPARTMENT AT UNIVERSITY OF NUSANTARA PGRI KEDIRI - Dwi Hayuningtias; Rika Riwayatiningsih; Dewi Kencanawati (Pusat Riset dan Inovasi Nasional, 2022)
In learning, an offline system (face-to-face) and an online system can be used to learn in order to process of acquiring knowledge. However, the world is now in total lockdown as a result of the Covid-19 virus, which has forced all activities, including education, to move to an online system. Students at University of Nusantara PGRI Kediri, particularly those in the English department, use a variety of online learning support applications, in order to facilitate online learning. One application that is used for frequent is Zoom Application. The purpose of this study is to find the use of Zoom application to support online learning, and the advantages and disadvantages of Zoom application during the pandemic time for English department students at University of Nusantara PGRI Kediri. This study used qualitative research as its technique. 22 first-graders (second semester) volunteered as subjects for data collection. Interview and questionnaire chosen as its data collecting technique. The findings of the data analysis display that the use of the zoom application can bridges the online learning as well as teacher and student interactions while on the other hand, zoom application has advantages and disadvantages that must be considered.